2019
DOI: 10.1108/ara-01-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Audit fees, perceived audit risk, and the financial crisis of 2008

Abstract: Purpose The purpose of this paper is to investigate how audit fees change in responding to the financial crisis of 2008. It also examines auditors’ perceived risk and how they priced the risk in the financial crisis. Design/methodology/approach Using a sample of 20,930 firm-year observations, this paper examines the change of audit fees before, during and after the financial crisis, as well as the relationship between audit fees and restatements. Furthermore, this study investigates whether this relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 26 publications
(53 reference statements)
4
48
0
4
Order By: Relevance
“…The changing economic conditions are challenging for audit companies and their clients as these changes will affect the company’s liquidity, risk and performance, which will ultimately affect audit fees (Chen et al , 2019). More specifically, there is a higher risk that the company may violate the conditions stipulated in the debt contract, and some companies, therefore, may go bankrupt.…”
Section: Covid-19 and Audit Feesmentioning
confidence: 99%
See 1 more Smart Citation
“…The changing economic conditions are challenging for audit companies and their clients as these changes will affect the company’s liquidity, risk and performance, which will ultimately affect audit fees (Chen et al , 2019). More specifically, there is a higher risk that the company may violate the conditions stipulated in the debt contract, and some companies, therefore, may go bankrupt.…”
Section: Covid-19 and Audit Feesmentioning
confidence: 99%
“…More specifically, there is a higher risk that the company may violate the conditions stipulated in the debt contract, and some companies, therefore, may go bankrupt. Higher risk levels and growing concerns of creditors will force auditors to adopt broader audit procedures and invest more in audit work when evaluating firms’ going concern assumptions (Ghosh and Pawlewicz, 2009; Noh et al , 2017; Zhang and Huang, 2013; Chen et al , 2019). During this pandemic, the growing demand for assurance and the increased risk of auditor litigation would increase the auditor’s effort and working hours (Karim and Zijl, 2013; Yuen et al , 2013).…”
Section: Covid-19 and Audit Feesmentioning
confidence: 99%
“…On the other hand, audit clients were coping with financial difficulties, and were likely to ask auditors to cut their fees. In most settings, audit fees increased – in Australia (Xu et al , 2013); China (Zhang and Huang, 2013); Sweden (Alexeyeva and Svanström, 2015) and the USA (Chen et al , 2019), for example. On the other hand, there were some settings where fees where lower such as Slovenia (Groff et al , 2017) and some US banks (Krishnan and Zhang, 2014).…”
Section: What To Expect In Auditing Crisismentioning
confidence: 99%
“…The researchers suggested that during the GFC, the risk associated with the probability of issuing an incorrect audit opinion is high due to the higher legal risks and reputation loss especially because of the increased regulatory pressure experienced during the credit crisis period. According to Chen et al (2019), prior studies on the audit risk model were carefully reviewed by scholars who confirmed there is a significant association between the primary factors of this model: inherent, control and detection risk. Based on Cahan and Sun (2015), Cahan and Zhang (2006) and Elder et al (2009), auditors' perceptions about audit risk are closely associated with changes in both inherent risk and control risk and thus ultimately, affect their performance in reducing detection risk (Kikhia, 2015).…”
Section: The Global Financial Crisis and Audit Fees: Theoretical Supportmentioning
confidence: 99%
“…Studies that use non-US markets' data tend to make comparisons between the crisis period and pre-crisis period providing evidence for audit risk premium during the financial crisis. A study conducted by Chen et al (2019) using a sample of 5636 firms operating in US markets for the years 2006-2011, examined the effect of the GFC on audit fees and the association between audit fees and the financial restatements. Furthermore, the study examined the extent to which the association between audit fees and restatements grew during the financial crisis.…”
Section: The Global Financial Crisis and Audit Fees: Theoretical Supportmentioning
confidence: 99%